Pencapaian dan Peningkatan Kemampuan Berpikir Kritis Siswa Kelas VIII SMP Melalui Pendekatan Pendidikan Matematika Realistik - Trivonia Bau, Anastasia; Loka Son, Aloisius; Patricia Wua Laja, Yosepha (Hexagon: Jurnal Ilmu dan Pendidikan Matematika, 2023)
The aim of this study was to compare the achievement and improvement of students' critical thinking skills through realistic mathematics education approaches and conventional learning. This study uses a quantitative method with a quasi-experimental approach. The research design used a pretest-posttest control group design. The experimental group learning used the PMR approach and the control group used conventional learning. This study was conducted in October 2022. The participants in this study were students of class VIII of a junior high school in Belu district. The sample in this study was 50 students consisting of two classes, each class consisting of 25 students. The research instrument was in the form of critical thinking ability tests and learning implementation observation sheets. Analysis of achievement data and improvement of necessary thinking skills using the Independent Samples t-test. The results of the study show that the achievement and improvement of students' mathematical necessary thinking skills who learn through a realistic mathematics education approach are better than students who learn with conventional approaches. This shows that learning with a realistic mathematics education approach can facilitate junior high school students critical thinking abilities